Impact of the transnationalization of the Syrian civil war on Turkey: conflict spillover cases of ISIS and PYD-YPG/PKK - PARLAR DAL, EMEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
This article examines how Turkey was affected by the conflict spillover effects of the Syrian civil war and its escalation in the last two years with the rise of the Islamic State in Iraq and Syria (ISIS) threat and the changing nature of the Kurdish insurgency. It seeks to assess the degree of the transnationalization of the Syrian civil war and its spread to Turkey by employing a theoretical framework borrowed from the conflict clustering literature. The first part will introduce the dual-embedded theoretical framework with its division of conflict spillover effects as intentional and unintentional. The second part tries to apply this dual-track framework to the Turkish case and, thus, seeks to test the conflict spillover factors on Turkey. The third part focuses on the two specific and major spillovers of the Syrian civil war, the ISIS threat and the rise of an embedded Kurdish insurgency, namely Democratic Union Party (PYD or Partiya Yekitiya Demokrat)-Peoples Protection Units (Yekineyen Parastina Gel or YPG)/Kurdistan Workers Party (Partiya Karkeren Kurdistane or PKK), and explains the conflict spillover processes of these two case studies under a triple framework, origin, diffusion and escalation and with reference to the division between intentional and unintentional spillover effects.